Will it skillet? : 53 irresistible and unexpected recipes to make in a cast-iron skillet - Shumski, Daniel (Workman Publishing, 2017)
"Discover a new world of cast-iron cooking. From Dan Shumski, who last applied his out-of-the-box food-loving sensibility to Will It Waffle?, here are 53 surprising, delicious, and ingenious recipes for the cast-iron skillet. Savor the simplicity of Toastwith Olive Oil and Tomato, because you just can't achieve that perfect oil-toasted crust in a toaster. For Homemade Corn Tortillas, no special equipment required--use the pan to flatten and cook them. (Then serve your tortillas with Single-Skillet Carnitas or Charred Tomato Salsa--or make Chilaquiles.) Take popcorn to another level with clarified butter. Enjoy a Spinach and Feta Dip that stays warm from the residual heat of the pan. Plus pastas that come together in one skillet--no separate boiling required; perfectly charred roasted vegetables; beautiful breads and pizzas; and luscious desserts from a giant chocolate chip cookie to the sophisticated Layered Crepe Torte with Dark Chocolate and Raspberry Jam. Includes detailed information on buying, seasoning, and caring for your cast-iron skillet--and turning it into a nonstick kitchen workhorse"--